The Side Effects of Gonadotropin Releasing Hormone Analog (Diphereline) in Treatment of Idiopathic Central Precocious Puberty - Zohreh Karamizadeh (Acta Medica Iranica, 2013)
Treatment of central precocious puberty (CPP) is the administration of GnRH analogs. Metabolic syndrome comprised metabolic disturbances that confer increased risk of (CVD) diabetes mellitus (DM) and cardiovascular disease. This study is a longitudinal prospective study in pediatric endocrinology clinic. 30 non-obese children with idiopathic CPP were involved. Total body weight, height, blood pressure, BMI and waist circumference of the patients along with their triglyceride (TG), total cholesterol (TC), low density lipoprotein (LDL), high density lipoprotein (HDL), fasting plasma sugar (FPS) were evaluated at the beginning and during 3 and 6 months GnRH analog therapy. All of the patients involved in this study were female with age 9.5±1.02 years. Waist circumference, weight and BMI were 69.3 cm, 37.21 kg, and 19.13 kg/cm2 before therapy and 72.25 cm, 40.11 kg, and 19.54 kg/m2 6 months after therapy respectively. Mean systolic and diastolic blood pressure of the patients before therapy was 96.83 mmHg, 66mmHg and after 6 months therapy was 98.66 mmHg, 89.63 mmHg respectively. Mean TG, LDL, HDL and FPS were 90.06 mg/dl, 91.6 mg/dl, 43.7 mg/dl and 89.6 mg/dl before therapy and 96.4 mg/dl, 93.1 mg/dl, 44.7 mg/dl and 91.36 after 6 months therapy respectively. GnRH analog therapy doesn't cause metabolic syndrome after 3 and 6 month therapy but it may cause hyperlipidemia and central obesity.